Distribution of polysaccharidic and proteinaceous gel−like particles in three cyclonic eddies in the Eastern Tropical North Atlantic - Devresse, Quentin; Becker, Kevin W.; Engel, Anja (Frontiers in Marine Science, 2024)
Transparent exopolymer particles (TEP) and Coomassie stainable particles (CSP), two prominent classes of gel−like particles in the ocean primarily produced by phytoplankton, play crucial roles in ecological and biogeochemical processes, influencing microbial nutrition, growth, and particle aggregation. The distribution of these particles is intricately linked to the spatiotemporal dynamics of phytoplankton. Mesoscale cyclonic eddies (CEs) are known to stimulate phytoplankton growth and influence particle transport, but their effects on TEP and CSP remain to be determined. In the Eastern Tropical North Atlantic (ETNA), we examined three CEs: one off the Mauritanian coast during summer (Mau), one offshore during winter (Sal), and another near Brava island during winter. Mau and Brava CEs were in their intensification/maturity phase, while the Sal CE was in its decay phase. Both TEP and CSP concentrations correlated with primary productivity, but TEP increased with chlorophyll−a concentration, whereas elevated CSP coincided also with the highest abundance of pico−nanophytoplankton (<20 µm), mainly Synechococcus. Both gels exhibited a positive correlation with bacterial biomass production, indicating their consumption by heterotrophic bacteria. TEP total area in the epipelagic waters of all CEs (Mau, Brava, and Sal) was elevated compared to surrounding waters, with on average 4, 2.5, and 1.6−fold higher values, respectively. However, no significant difference in TEP size distribution was observed within any CEs and their surroundings. Similarly, CSP total area increased in the epipelagic waters of Mau and Brava CEs, with on average 5 and 2.4−fold higher values, respectively, compared to surrounding waters. CSP particles were notably larger in these two eddies, while the Sal CE showed no significant difference from surrounding waters in CSP abundance and size. Overall, TEP and CSP exhibited distinct responses to CEs, with increased concentrations during their intensification/maturation stage and remineralization dominating during their decaying stage.